Rothmund-Thomson syndrome, a disorder far from solved - Martins, Davi Jardim; Di Lazzaro Filho, Ricardo; Bertola, Debora Romeo; Hoch, Nícolas Carlos (Frontiers in Aging, 2023)
Rothmund-Thomson syndrome (RTS) is a rare autosomal recessive disorder characterized by a range of clinical symptoms, including poikiloderma, juvenile cataracts, short stature, sparse hair, eyebrows/eyelashes, nail dysplasia, and skeletal abnormalities. While classically associated with mutations in the RECQL4, which encodes a DNA helicase involved in DNA replication and repair, three additional genes have been recently identified in RTS: ANAPC1, encoding a subunit of the APC/C complex; DNA2, which encodes a nuclease/helicase involved in DNA repair; and CRIPT, encoding a poorly characterized protein implicated in excitatory synapse formation and splicing. Here, we review the clinical spectrum of RTS patients, analyze the genetic basis of the disease, and discuss molecular functions of the affected genes, drawing some novel genotype-phenotype correlations and proposing avenues for future studies into this enigmatic disorder.